Holocene variations in the Asian monsoon inferred from the geochemistry of lake sediments in central Tibet - Morrill, C; Overpeck, JT; Cole, JE; Liu, KB; Shen, CM; Tang, LY (唐领余) (Quaternary Research, 2006)
We present a record of monsoon variations for the early and middle Holocene that is inferred from the geochemistry of sediment cores from Ahung Co, a lake in central Tibet. The resolution of this record is better than 50 yr and the age model is derived from radiocarbon ages of terrestrial charcoal, which eliminates errors associated with the lake hard-water effect. We made down-core geochemical measurements of % carbonate, % organic carbon, C/N and delta C-13 of bulk organic matter, delta C-13 and delta O-18 of carbonate, and % dolomite. Proxy calibration and modern water-balance reconstruction show that these are proxies for lake depth and the amount of monsoon precipitation. We find that lake level and monsoon precipitation have been decreasing at Ahung Co since the early Holocene (similar to 7500 cal yr B.P.). Superimposed on this trend are rapid declines in monsoon rainfall at 7000-7500 and 4700 cal yr B.P. and seven century-scale wet-dry oscillations. The cores do not contain sediment from the last similar to 4000 yr. Surface sediments from the lake accumulated during the 20th century, however. From this, we argue that lake levels have risen again recently following a late Holocene dry period. (c) 2005 University of Washington. All rights reserved.